A comparative analysis between sequential boost and integrated boost intensity-modulated radiation therapy with concurrent chemotherapy for locally-advanced head and neck cancer. Issue 1 (December 2017) - Vlacich, Gregory; Stavas, Mark; Pendyala, Praveen; Chen, Shaeu-Chiann; Shyr, Yu; Cmelak, Anthony
Abstract Background Planning and delivery of IMRT for locally advanced head and neck cancer (LAHNC) can be performed using sequential boost or simultaneous integrated boost (SIB). Whether these techniques differ in treatment-related outcomes including survival and acute and late toxicities remain largely unexplored. Methods We performed a single institutional retrospective matched cohort analysis on patients with LAHNC treated with definitive chemoradiotherapy to 69.3 Gy in 33 fractions. Treatment was delivered via sequential boost (n  = 68) or SIB (n  = 141). Contours, plan evaluation, and toxicity assessment were performed by a single experienced physician. Toxicities were graded weekly during treatment and at 3-month follow up intervals. Recurrence-free survival, disease-free survival, and overall survival were estimated via Kaplan-Meier statistical method. Results At 4 years, the estimated overall survival was 69.3% in the sequential boost cohort and 76.8% in the SIB cohort (p  = 0.13). Disease-free survival was 63 and 69% respectively (p  = 0.27). There were no significant differences in local, regional or distant recurrence-free survival. There were no significant differences in weight loss (p  = 0.291), gastrostomy tube placement (p  = 0.494), or duration of gastrostomy tube dependence (p  = 0.465). Rates of acute grade 3 or 4 dysphagia (82% vs 55%) and dermatitis (78% vs 58%) were significantly higher in the SIB group (p  < 0.001 andp  = 0.012 respectively). Moreover, a greater percentage of the SIB cohort did not receive the prescribed dose due to acute toxicity (7% versus 0, p  = 0.028). Conclusions There were no differences in disease related outcomes between the two treatment delivery approaches. A higher rate of grade 3 and 4 radiation dermatitis and dysphagia were observed in the SIB group, however this did not translate into differences in late toxicity. Additional investigation is necessary to further evaluate the acute toxicity differences.